Media as a fourth pillar of democracy needs to engage more issues that affect human development - GP Pandey (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Media is an important and inseparable part of a democratic society. The media is regarded as the fourth pillar of democracy because often time's people assume that the media is more neutral and freer from elements of state power, in contrast with the previous three pillars which are all oriented to power. In a democratic setup the media can act as a bridge between the government and the people. Its true function is to inform the people, and the measure of freedom it enjoys, depends upon the way it discharges that function. The people have a right to be informed freely and fully, and for that the media is accountable neither to the state, nor to the proprietor, but to the people. The media, known as the fourth pillar of democracy, has a huge impact on the society. The effects are of course, positive as well as negative. Media is such a powerful tool that it literally governs the direction of our society today. It is the propeller as well as the direction provider of the society. Opinions can change overnight and celebrities can become infamous with just one wave by the media. The media apts as a deterrent on corrupt practices and keeps a check on the working of the government. But, sometimes under political pressure, pressure of corporate entities, etc. the media oversteps its avowed mandate. Media has significantly promoted social causes like literacy. health management, anti-dowry practices, discouraging female feticide, AIDS awareness, etc. As a fourth pillar of democracy, the media of today has an all embracing role to act against the injustice, oppression, misdeeds and partiality of our society. Thus. in a democratic society. the media is charged with the responsibility to provide the public with background information about the issues. How to cite this article: Pandey GP. Media as a Fourth Pillar of Democracy Needs to Engage more Issues that Affect Human Development. J Adv Res Jrnl Mass Comm 2020; 7(4): 15-20.